2012
DOI: 10.4314/njp.v39i2.6
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection in hospitalized under-5 children with acute watery diarrhoea in Calabar, Nigeria.

Abstract: Background: The signs and symptoms of HIV/AIDS in children are not quite distinct because of similarities in clinical presentation between HIV infection and endemic tropical diseases. Diarrhoea, one of the cardinal symptoms of HIV/AIDS, is a common childhood disease. Objective: This study was conducted to find the prevalence of HIV infection among children admitted with acute watery diarrhoea in our diarrhoea treatment and training unit. Method: Consecutive children aged below 5 years admitted into the unit wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Calabar was one of the earliest centres in Nigeria to report paediatric AIDS [9], but presently has only few children enrolled into antiretroviral (ARV) programme. A more disturbing fact is that a recent study of the prevalence of HIV in children with acute watery diarrhoea in the centre was found to be as high as 5% [10].…”
Section: Introduction mentioning
confidence: 99%
“…Calabar was one of the earliest centres in Nigeria to report paediatric AIDS [9], but presently has only few children enrolled into antiretroviral (ARV) programme. A more disturbing fact is that a recent study of the prevalence of HIV in children with acute watery diarrhoea in the centre was found to be as high as 5% [10].…”
Section: Introduction mentioning
confidence: 99%
“…Ntia et al reported HIV prevalence of 5.6% among hospitalized under-fives with acute watery diarrhoea in a tertiary health facility in Cross River State. 14 It is worthy of note that even though there was a low request for investigations for diarrhoea disease by the health care providers, the performance was quite high among those in whom the requests were made. This indicates a good compliance by caregivers to conduct investigations when requested.…”
mentioning
confidence: 99%